Implementasi Modul ILO-SCORE UMKM Warung Sembako ‎Razka Dalam Aspek Tata Letak dan Kebersihan (5S) dan Aspek ‎Pemasaran di Daerah Perbatasan, Kalimantan Barat ‎ - Kristianto, Aloysius Hari; Anggreni, Astri; Iskandarsyah, Triyana (Indra Institute Research & Publication, 2023)
The community service initiative, in conjunction with ILO-Score, aims to support MSME players in the Razka basic food shop. These business players are still simple in terms of governance, layout, and public advertising. The condition that exists is that the things being traded are still placed randomly and are unknown to the surrounding population. The work program implemented is the 5S idea and location mapping on Google maps for the early phases of digital marketing. The participation of students in this support creates new behaviors that business players have not before exercised. Business actors may use their understanding of net production to improve their operations.